ANALISIS UJI PENYERAPAN AIR DAN STRUKTUR MIKRO KOMPOSIT LAMINATE HYBRID SERAT SISAL DAN BATANG PISANG DENGAN MATRIK EPOXY - I Putu Krishna Artha Sastra; Nasmi Herlina Sari; S. Sujita (Universitas Mataram, 2013)
The purpose of this study is to investigate and analyze about absorption properties of the composite laminate, microstructure hybrid sisal and banana fiber with epoxy matrix. Composite manufacturing was done by hand lay-up method with a ratio of fiber volume fraction of sisal and banana trunks 0:40, 10:30, 15:25, 20:20, 30:10, 40:0 (%) With direction of sisalana agave fiber orientation and banana fiber by fiber length according to the mold. Specimen testing was done by the water absorption test with the standard ASTM D571-8,. Test results obtained from the average water absorption properties of composites with the highest ratio of fiber volume fraction of 40%: 0% is 42.4% while the lowest average water absorption properties contained in the composite with fiber volume fraction of 0%: 40%, with percentage of 11.5%. Therefore we can conclude the increasing volume fraction of sisal fiber withidirection of fiber orientation, the lower of water absorption properties and conversely increasing the volume of woven banana fiber orientation, the higher of water absorptionproperties.